Death and digital media - Arnold, Michael, author.
1 online resource (x, 178 pages)
Keywords: "Death and Digital Media provides a critical overview of how people mourn, commemorate and interact with the dead through digital media. It maps the historical and shifting landscape of digital death, considering a wide range of social, commercial and institutional responses to technological innovations. The authors examine multiple digital platforms and offer a series of case studies drawn from North America, Europe and Australia. The book delivers fresh insight and analysis from an interdisciplinary perspective, drawing on anthropology, sociology, science and technology studies, human-computer interaction, and media studies. It is key reading for students and scholars in these disciplines, as well as for professionals working in bereavement support capacities."--Provided by publisher.